Komunikasi Ritual Sembahyang Rebut bagi Etnis Cina di Kecamatan Parittiga Bangka Barat - Enjelly, Enjelly; Azeharie, Suzy (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Prayer is a religious activity carried out consciously to establish a relationship with the creator of the form of prayer. In religious traditions, prayer is associated with a ritualistic nature as a form of human communication with the Creator. One of the Chinese ethnic prayer celebrations in West Bangka, especially Parittiga subdistrict, is the Rebut Prayer Celebration. Sembahyang Rebut is a celebratory ritual to honor ancestral spirits which is held every 15th of the seventh month in the lunar calendar. During the Sembahyang Sebut celebration, many ethnic Chinese call this ritual the ghost moon festival or Chit Ngiat Pan, where it is believed that the spirits of ancestors return to the human world. The aim of this research is to find out how the ritual process of the Sembahyang Rebut celebration is and what symbolic meaning is contained in the Sembahyang Rebut celebration. The theory used in this research is the theory of ritual communication and symbolic meaning. The research method used is a descriptive qualitative phenomenology approach. The data that will be described was obtained from interviews with three sources. The conclusion of this research is that the Rebut Prayer Celebration is a tradition passed down from generation to generation which has the form of a symbol of balance with the intention of giving and receiving, which means that if we freely pay respects to the spirits of ancestors and others, we will receive blessings and good fortune. Sembahyang adalah kegiatan keagamaan yang dilakukan secara sadar guna menjalin hubungan dengan sang pencipta berbentuk doa. Dalam tradisi keagamaan, sembahyang dikaitkan dengan sifat ritualistik sebagai bentuk komunikasi manusia kepada sang pencipta. Salah satu perayaan sembahyang bagi etnis Tionghoa di Bangka Barat khususnya kecamatan Parittiga adalah perayaan Sembahyang Rebut. Sembahyang Rebut adalah ritual perayaan untuk menghormati arwah leluhur yang diadakan setiap tanggal 15 bulan tujuh dalam penanggalan kalender lunar. Dalam perayaan Sembahyang Rebut banyak etnis Tionghoa yang menyebut ritual ini sebagai festival bulan hantu atau Chit Ngiat Pan yang dipercayai bahwa arwah leluhur akan kembali ke alam manusia. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana proses ritual perayaan Sembahyang Rebut dan apa makna simbolik yang terkandung dalam perayaan Sembahyang Rebut. Teori yang digunakan dalam penelitian ini adalah teori komunikasi ritual dan makna simbolik. Metode penelitian yang digunakan adalah fenomenologi pendekatan kualitatif deskriptif. Data diperoleh dari hasil wawancara dengan tiga narasumber. Penelitian menemukan bahwa Perayaan Sembahyang Rebut merupakan tradisi turun temurun yang memiliki bentuk simbol keseimbangan dengan maksud memberi dan menerima yang artinya adalah apabila kita dengan lapang hati memberi penghormatan kepada arwah leluhur dan lainnya maka kita akan menerima berkah dan rezeki yang lancar.